Developing Corpus-Based English Teaching Materials for Hotel Staff - Nurdiana, Nurdiana (English Journal Antartika, 2025)
Proficiency in English is essential for individuals working in the hospitality industry, including in Indonesia. However, many Indonesian hotel- staff struggle to use English appropriately in workplace settings despite being employed in five-star establishments. In the context of English Language Teaching (ELT), there is a need for instructional materials that incorporate relevant linguistic features and pragmatic usage tailored to the specific contexts and situations of the hospitality industry. This study, therefore, aimed to develop English teaching materials that emphasize linguistic elements and expressions frequently used in hospitality settings. A corpus linguistics approach was adopted to ensure the materials reflect authentic and commonly used language in real-life hospitality interactions. Employing a qualitative-descriptive design, the study utilized the Corpus of Contemporary American English (COCA) to identify frequently occurring English expressions within hospitality discourse. The findings revealed a range of commonly used expressions that are contextually relevant to the hospitality sector. Based on these results, it is recommended that English teaching materials for hotel staff be developed using corpus-based approaches to promote more authentic and natural language use in professional hospitality environments.